Musculoskeletal disorders among 'Canting' batik workers in Kuala Terengganu - Azizah, Endut (2012)
In a typical procedure of “canting” process, the batik workers have to stand for a long period of time and sometimes they have to bend their bodies. If these techniques of working are practiced for a long period of time, it is believed to cause back pain and musculoskeletal disorders (MSDs) problems among the workers and also affect the productivity of their work. This paper presents a study in batik industry with the objective of determining any musculoskeletal disorders among batik workers caused by working tasks in “canting” process. The study was conducted in Kuala Terengganu area where MSDs symptoms of batik workers were identified through questionnaires adopted and modified from a Standardized Nordic Questionnaire (SNQ) for analysis of musculoskeletal symptoms. Our study showed that 77.8 % of the respondents suffered from at least one musculoskeletal pain at the back, shoulder, foot, ankle, knee, hand or wrist. The most common symptoms were pain over the back and wrist. Therefore, it is necessary to improve on both posture and “canting” tools in order to provide a maximum comfort to the workers and consequently enhance the productivity.